Best-practice EVA : the definitive guide to measuring and maximizing shareholder value - Stewart, G. Bennett, III, 1953- (Hoboken, New Jersey : Wiley, 2013)
The return to value tells the new EVA story from the ground up. Stewart covers EVA essentials-the classic economic profit version of EVA-in the first three chapters of the book.-showing readers how how simple and intuitive EVA really is, how it is defined and why it is better than all other measures of corporate profit and cash flow. You discover how it naturally guides managers into making all the right decisions-the ones that will truly maximize value. You even see how to use it in profit-sharing bonus plans that create the powerful incentives of an owner.
EVA 101 -- EVA and value -- Accounting for value -- What's wrong with RONA?
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Economic value added; Corporations -- Valuation; Stockholder wealth; BUSINESS & ECONOMICS -- Investments & Securities -- General; Corporations -- Valuation; Economic value added; Stockholder wealth; Electronic books; Electronic books